Developing Streamflow Model for Sustainable Rural Water Supply at Ndimoko, Imo State, Nigeria - Okoro, B. C.; Uzoukwu, R. A. (European Journal of Sustainable Development, 2014)
Streamflow model of Imo River at Ndimoko was developed using statistical method of least squares. High and positive values of coefficient of correlation (r) of 0.953 and coefficient of determination (r2)) of 0.908 were obtained. The standard error of estimate (SQ.h) has small value of 1.82 indicating that the regression model fits the data. The model represents the nonlinear relationship between annual maximum discharge and annual maximum stage. The model developed is necessary for the design of dam, estimation of the size of reservoir, water conservation methods, potable water supply, flood estimation, wild life protection and recreational use of water in the locality. In other words, this model will play an important role in ensuring that future planning and management of water in a rural area is scientifically based and efficiently made. Recommendations are made that hydrologic modeling be applied in water resources planning, design and management activities for environmental sustainability. Keywords: Maximum Stage, Maximum Discharge, Coefficient of Correlation, Coefficient of Determination, Water Supply.